2013
DOI: 10.1364/ol.38.005036
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal nonlinearity and optical bistability in a graphene–silicon waveguide resonator

Abstract: We report observation of optical bistability and enhanced thermal nonlinearity in a graphene-silicon waveguide resonator. Photo-induced Joule heating in the graphene layer gives rise to a temperature increase in the silicon waveguide core and a corresponding thermo-optic shift in the resonance of the Fabry-Perot resonator. Measurement of the nonlinear resonance spectra showed a 9-fold increase in the effective thermal nonlinear index due to the graphene layer compared with a bare silicon waveguide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 12 publications
2
25
1
3
Order By: Relevance
“…As mentioned before, owing to its broadband absorption or electrical conductivity, the 2D material can be used as an efficient optical or electrical heater. The excited carriers, either optically or electrically, can transfer their energy to phonons during the relaxation process, and increase the temperature of the material. Also, owing to their high thermal conductivity (e.g., 10 3 W m –1 K –1 for graphene, much higher than that of the copper) at room temperature, the 2D material can readily spread the heat to the surrounding material, and can function as a flexible heat generator and conductor .…”
Section: Optical Modulation With 2d Materialsmentioning
confidence: 99%
“…As mentioned before, owing to its broadband absorption or electrical conductivity, the 2D material can be used as an efficient optical or electrical heater. The excited carriers, either optically or electrically, can transfer their energy to phonons during the relaxation process, and increase the temperature of the material. Also, owing to their high thermal conductivity (e.g., 10 3 W m –1 K –1 for graphene, much higher than that of the copper) at room temperature, the 2D material can readily spread the heat to the surrounding material, and can function as a flexible heat generator and conductor .…”
Section: Optical Modulation With 2d Materialsmentioning
confidence: 99%
“…We theoretically investigated the optical bistability of reflection at the interface between graphene and Kerr-type nonlinear substrates 31 . Horvath et al reported observation of optical bistability and enhanced thermal nonlinearity in a graphene–silicon waveguide resonator 32 . Peres et al found that a single layer of graphene showed an optical bistability in the lower THz frequency range for nonlinear graphene suspending in air 33 .…”
mentioning
confidence: 99%
“…However, the magnitude of nonlinearity (n 2 ) is on the order of 10 –9 μm 2 /mW 3 . Photothermal effects are known to provide much larger nonlinear responses, with the effective nonlinear coefficient n 2 approaching 10 –6 μm 2 /mW 5 . From a simple estimation based on n = n 0 + n 2 I, in which n is the overall refractive index, n 0 is the linear index, n 2 is the nonlinear index, and I is excitation intensity, to create 10% nonlinear deviation from the linear response, an exceedingly high excitation intensity in the order of 10 5 mW/μm 2 is necessary.…”
Section: Introductionmentioning
confidence: 99%